Basic Newborn Resuscitation: Health Care Providers' Level of Knowledge and Factors Affecting in the Hospitals of Southern Ethiopia. Issue 4 (December 2020) - Mersha, Abera; Shibiru, Shitaye; Gultie, Teklemariam; Degefa, Nega; Bante, Agegnehu
Background: The health care provider's knowledge and clinical experience determine the success of newborn resuscitation. Adequate knowledge of health care providers on newborn resuscitation is vital to avert adverse neonatal outcomes. But, a few studies assessed health care providers' level of knowledge on basic newborn resuscitation, including Ethiopia. Objective: To assess the health care provider's level of knowledge on basic newborn resuscitation and factors affecting it. Methods: In this cross-sectional survey, 445 health care providers involved by using a simple random sampling method from the hospitals of southern Ethiopia. The data were collected by self-administered questionnaires and an observational checklist. A binary logistic regression model was used and P -value < .05 was considered to declare a statistically significant association. Results: Health care providers with an adequate level of knowledge on basic newborn resuscitation indicated 76.2% (95% CI [72.2%, 80.3%]). Age, training, recent involvement in basic newborn resuscitation, and the well-equipped facility had shown significant association. Conclusions: This study indicated that adequate knowledge of health care providers on basic newborn resuscitation was optimum. Hence, health care providers train periodically, and the health facilities should equip with materials to provide essential life support for the newborns.